2004
DOI: 10.1152/ajplung.00341.2003
|View full text |Cite
|
Sign up to set email alerts
|

Myosin light chain phosphorylation and pulmonary endothelial cell hyperpermeability in burns

Abstract: Major cutaneous burns result in not only localized tissue damage but broad systemic inflammation causing organ system damage distal to the burn site. It is well recognized that many problems result from the release of inflammatory mediators that target vascular endothelial cells, causing organ dysfunction. The pulmonary microvessels are particularly susceptible to functional abnormalities as a direct consequence of exposure to burn-induced inflammatory mediators. Traditional therapeutic intervention is quite o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
43
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
4
43
0
Order By: Relevance
“…We also report that inhibition of ROCK attenuates the PMN-stimulated increases in endothelial isometric tension. These data are concordant with our previous reports that ROCK inhibition attenuates PMN-induced actin polymerization in endothelial cells (8) and dual phosphorylation of MLC caused by inflammatory stimuli (41). However, it is also worth noting that we observed a lag between ca-ROCKinduced MLC phosphorylation (noticeably increased at 30 min) and force development (starting at 10 min), indicating that the initial stage of ROCK-mediated contraction may involve other mechanisms that rapidly and transiently affect cell tension.…”
Section: Discussionsupporting
confidence: 92%
“…We also report that inhibition of ROCK attenuates the PMN-stimulated increases in endothelial isometric tension. These data are concordant with our previous reports that ROCK inhibition attenuates PMN-induced actin polymerization in endothelial cells (8) and dual phosphorylation of MLC caused by inflammatory stimuli (41). However, it is also worth noting that we observed a lag between ca-ROCKinduced MLC phosphorylation (noticeably increased at 30 min) and force development (starting at 10 min), indicating that the initial stage of ROCK-mediated contraction may involve other mechanisms that rapidly and transiently affect cell tension.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that activated neutrophils induce tyrosine phosphorylation of VE-cadherin and ␀-catenin followed by gap formation and hyperpermeability (25). Furthermore, we found that application of plasma from burned rats to cultured microvascular endothelial cells induced MLC phosphorylation-dependent permeability increases and actin stress fiber formation (23).…”
mentioning
confidence: 77%
“…Characteristic phenomena resulting from endothelial cell exposure to various agonists are phosphorylation of myosin light chain (MLC), actomyosin contractile forces, and modification/reorganization of the AJ (23)(24)(25)27). We have shown that activated neutrophils induce tyrosine phosphorylation of VE-cadherin and ␀-catenin followed by gap formation and hyperpermeability (25).…”
mentioning
confidence: 99%
“…A rise in proinflammatory cytokines is associated with MLCK activation, and it has been shown that TNF-␣, IL-1␀, and lymphotoxin-like inducible protein that competes with glycoprotein D for herpesvirus entry mediator on T cells (LIGHT) can upregulate MLCK transcription (2,12,25,29,30,36). Furthermore, increased MLCK activation has been linked to intestinal permeability after burn injury or chronic ethanol exposure alone (29,50). Traumatic injury, like burn, causes an overexuberant systemic inflammatory response characterized by a rise in systemic and tissue levels of IL-6, TNF-␣, and IL-1␀ (22,34,43,44).…”
mentioning
confidence: 99%